Informal self-employment in Kazakhstan - Altay Mussurov; G. Reza Arabsheibani (IZA Journal of Labor & Development, 2015)
We use data from the Kazakhstan Labour Force Survey (KLFS) for the period 2006-2011 to examine factors that determine informality amongst self-employed men and women. In addition, the paper examines the response of informality propensities to the recent global crisis. The decomposition suggests that the reduction in the predicted probabilities of being informal is mainly attributable to the unexplained component. Individual characteristics have played a relatively small role, except for changes in tenure, hours of work and education.
Keywords: P29; O17; 330; Self-employment; Informality; Gender; Transition